Bedtime Stress Increases Sleep Latency and Impairs Next-Day Prospective Memory Performance - Goldberg, Zoë-lee; Thomas, Kevin G. F.; Lipinska, Gosia (Frontiers in Neuroscience, 2020)
The cognitive construct of prospective memory (PM) refers to the capacity to encode, retain, and execute delayed intentions (e.g., to remember to buy milk on the way home). Although previous research suggests PM performance is enhanced by healthy sleep, conclusions tend to be drawn based on designs featuring ecologically unnatural manipulations (e.g., total sleep deprivation). This study investigates whether a more common everyday experience (bedtime stress) affects next-day PM performance, and in so doing also contributes to the heretofore inconsistent literature on stress and prospective memory. Forty young adults received PM task instructions and were then assigned to either a Stress condition (exposure to a laboratorybased acute psychosocial stressor; n = 20, 9 women) or a Non-Stress condition (exposure to a non-stressful control manipulation; n = 20, 12 women). After completing the experimental manipulation, all participants had their objective sleep quality measured over a full night of polysomnographic monitoring. Upon awakening, they completed the PM task. Analyses detected significant between-group differences in terms of stress outcomes, sleep quality, and PM performance: Participants exposed to the manipulation experienced heightened signs of stress (captured using a composite variable that included self-report, psychophysiological, and endocrinological measures), had longer sleep latencies and poorer sleep depth, and displayed significantly longer reaction times to PM cues. An interaction between experimental condition (being exposed to the stressor) and disrupted sleep (longer sleep latency) significantly predicted poorer next-day PM reaction time. We interpret these findings as indicating that bedtime stress, which leads to heightened pre-sleep arousal, affects sleep processes and, consequently, the deployment of attentional resources during next-day execution of a delayed intention.